Pendampingan Strategi Pemasaran dan Branding Digital Pada Usaha Molen Onde-Onde Mini Kangen di Kota Palangka Raya - Sylvia Putri; Erli Agustina; Josefa Angelita; Sunatalia Sunatalia; Iwan Christian; Theresia Mentari (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas KH. A. Wahab Hasbullah, 2025)
Micro, Small and Medium Enterprises in Palangka Raya City, including the Molen Onde-Onde Mini Kangen business, face the challenges of digital literacy and weak branding, thereby limiting market expansion. This community service activity focuses on assisting digital marketing and branding strategies to overcome this issue. The aim is to increase digital marketing capacity, create a strong brand identity, and expand the business' market reach. The method used includes intensive mentoring for six weeks with a participatory approach, consisting of initial observation, Instagram social media marketing training, logo and visual identity design, creation of promotional content in the form of videos, as well as implementation and evaluation. The results of the activity showed a significant increase in partners' understanding of digital marketing, the creation of a new logo and business Instagram account, as well as an increase in daily income from IDR 800,000 to IDR 1,200,000. This activity proves that structured assistance can empower business actors to adopt digital strategies effectively and sustainably.